Power supply for internet of things (IoTs) - Christopher, Gabrian (Nanyang Technological University, 2021)
Smart contact lens is a promising wearable device in the future for various applications especially in the biomedical fields. Powering the contact lens using conventional batteries has been a major challenge due to the paramount safety regulations imposed for wearable devices worn on the eye. In this project, a safe, flexible, aqueous battery is studied and fabricated. Prussian Blue Analogues (PBAs) are chosen as the active material for the battery’s electrode. The battery is designed to utilize tear fluid for its electrolyte solution. The battery’s performance is tested and characterized using electrochemical tests such as cyclic voltammetry (CV) and galvanostatic cycling with potential limitation (GCPL). The battery shows a specific capacity of 55.73 mAh/g in 1M KCl solution. In addition, a wireless power transfer concept is also briefly discussed to charge the fabricated battery.